2017
DOI: 10.1111/imr.12586
|View full text |Cite
|
Sign up to set email alerts
|

The renaissance of anti‐neoplastic immunity from tumor cell demise

Abstract: Cancer therapies can temporarily reduce tumor burdens by inducing malignant cell death. However, cancer cure is still far from realization because tumors often gain resistance to current treatment and eventually relapse. Accumulating evidence suggests that successful cancer interventions require anti-tumor immunity. Therapy-induced cell stress responses ultimately result in one or more cell death modalities, including apoptosis, autophagy, necroptosis, and pyroptosis. These irreversible dying processes are acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 143 publications
(304 reference statements)
0
46
0
Order By: Relevance
“…In this way, ICD-inducing chemotherapy drugs not only kill cancer cells, but also activate anticancer immunity that may potentiate the therapeutic efficacy of immunotherapy (22). However, all the known ICD markers do not always translate into strong in vivo antitumor immunity, and systemic evaluation of the ICD features of currently approved drugs have yielded inconsistent results due to tumor-intrinsic variation of capacities of some cellular functions such as autophagy or necroptosis (19,23,24). Currently, there are several reporter systems used for ICD inducer drug screening, such as fluorescent biosensor of CRT-GFP or HMGB1-GFP, ATP, and ELISA measurement of HMGB1 (25).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, ICD-inducing chemotherapy drugs not only kill cancer cells, but also activate anticancer immunity that may potentiate the therapeutic efficacy of immunotherapy (22). However, all the known ICD markers do not always translate into strong in vivo antitumor immunity, and systemic evaluation of the ICD features of currently approved drugs have yielded inconsistent results due to tumor-intrinsic variation of capacities of some cellular functions such as autophagy or necroptosis (19,23,24). Currently, there are several reporter systems used for ICD inducer drug screening, such as fluorescent biosensor of CRT-GFP or HMGB1-GFP, ATP, and ELISA measurement of HMGB1 (25).…”
Section: Introductionmentioning
confidence: 99%
“…[75][76][77][78][79] During ICD, dendritic cells (DCs) capture the released damaged-associated molecular patterns (DAMPs) and tumor-associated antigens (TAAs), then processed and presented to adaptive immune cells to activate specific immune response. 76,[79][80][81] Researchers have recognized the potential benefits of PTT when it was introduced to compensate for some inherent drawbacks of immunotherapy. Nanomaterials for PTT can be further modified with immunostimulants or other immune drugs to enhance the whole body's antitumor immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…A key factor for tumor cells to evade antitumor immune surveillance lies in the complex immunosuppressive microenvironment, which is formed through downregulation of tumor antigens and production of immunosuppressive mediators [1,2]. Great progress has been made in modern immunotherapy by recognizing immune checkpoint [3][4][5] and adopting tumor vaccine [6][7][8], which suggested that elucidating the antitumor immune-related mechanisms is crucial to initiate a clinically meaningful antitumor immune response.…”
Section: Introductionmentioning
confidence: 99%